Hurricanes of the North Atlantic : climate and society - Elsner, James B. (Oxford University Press, 1999)
1. Hurricane Characteristics. 2. Hurricane Categories and Impacts. 3. Hurricane Climate Data. 4. North Atlantic Hurricanes. 5. Tropical Only Hurricanes. 6. Baroclinically Enhanced Hurricanes. 7. Major Hurricanes. 8. U.S. Hurricanes. 9. Hurricanes of Puerto Rico, Jamaica, and Bermuda. 10. Hurricane Cycles and Trends. 11. Hurricane Return Periods. 12. Hurricanes of the Early 1990s. 13. History of Seasonal Hurricane Forecasting. 14. Seasonal Forecast Models. 15. Sub Basin Forecast Models. 16. Prospects for Extended Range Outlooks. 17. People at Risk. 18. Property at Risk. 19. Catastrophe Insuranc.